Morphology and Phylogeny of Hyalinostachys dehongensis sp. nov., a Bambusicolous Species From Yunnan Province, China - Yu‐Rong Yan; Li‐Su Han; Gang‐Ya Xu; Samantha C. Karunarathna; Nakarin Suwannarach; Jaturong Kumla; A. N. W. Sumedha Thushari; Sajad Ali; Dong‐Qin Dai; Saowaluck Tibpromma (New Zealand Journal of Botany, 2026)
China has abundant bamboo resources, among which Yunnan Province is one of the regions with the greatest number of species. The unique natural and geographic advantages provide an excellent environment for fungal growth. This study collected and isolated saprobic hyphomycetes associated with dead bamboo in Yunnan Province, China. Based on detailed morphological comparisons and multi‐locus phylogenetic analyses of combined LSU, ITS, tef 1‐ α , rpb 2, tub 2, and cmdA sequence data, the new isolates are introduced here as a novel species, Hyalinostachys dehongensis in the family Stachybotryaceae of Ascomycota. A complete description, morphological illustrations, and phylogenetic analysis results for the new species are provided. In addition, this species is introduced here as the second species since this genus was introduced in 2020.

Eutrophication and predation mediate zooplankton diversity and network structure - Yun Li; Rong Wang; Haojie Su; Jianjun Wang; Ping Xie; Feizhou Chen (Limnology and Oceanography, 2022)
Anthropogenic activities such as eutrophication and fishing have prominent effects on freshwater ecosystems. However, the ways in which ecosystem function and biodiversity respond to multiple drivers from eutrophication and top‐down predation remains inconclusive. We studied zooplankton communities in 102 subtropical shallow lakes in the eastern plain of China and further examined the joint effects of nutrient enrichment and predation on biodiversity and ecological networks. We found that alpha diversity was negatively influenced by nutrient conditions (such as total phosphorus and total nitrogen [TN]), whereas beta diversity (β‐diversity) was positively related to nutrients and was also structured by omnivorous fish showing a unimodal pattern. Furthermore, the network skewness of zooplankton increased with nutrient enrichment, especially TN, and was negatively related to omnivorous fish. This skewness is more sensitive than β‐diversity, whereas negative skew is primarily caused by omnivorous fish. Our results demonstrated that top‐down effects were dominant for zooplankton communities and resulted in structural adjustment of zooplankton communities, mainly with an increase in fish predation. A negative skewed network indicates the presence of more generalist species and stronger connections among the zooplankton assemblages, as well as decreased β‐diversity.

Simultaneous detection of multiple bacterial and viral aquatic pathogens using a fluorogenic loop‐mediated isothermal amplification‐based dual‐sample microfluidic chip - Qian‐Jin Zhou; Jian‐Fei Lu; Xiu‐Rong Su; Jing‐Lei Jin; Shang‐Yang Li; Yan Zhou; Lei Wang; Xin‐Bin Shao; Yao‐Hua Wang; Mao‐Cang Yan; Ming‐Yun Li; Jiong Chen (Journal of Fish Diseases, 2021)
Rapid and user‐friendly diagnostic tests are necessary for early diagnosis and immediate detection of diseases, particularly for on‐site screening of pathogenic microorganisms in aquaculture. In this study, we developed a dual‐sample microfluidic chip integrated with a real‐time fluorogenic loop‐mediated isothermal amplification assay (dual‐sample on‐chip LAMP) to simultaneously detect 10 pathogenic microorganisms, that is Aeromonas hydrophila , Edwardsiella tarda , Vibrio harveyi , V. alginolyticus , V. anguillarum , V. parahaemolyticus , V. vulnificus , infectious hypodermal and haematopoietic necrosis virus, infectious spleen and kidney necrosis virus, and white spot syndrome virus. This on‐chip LAMP provided a nearly automated protocol that can analyse two samples simultaneously, and the tests achieved limits of detection (LOD) ranging from 10 0 to 10 –1 pg/μl for genomic DNA of tested bacteria and 10 –4 to 10 –5 pg/μl for recombinant plasmid DNA of tested viruses, with run times averaging less than 30 min. The coefficient of variation for the time‐to‐positive value was less than 10%, reflecting a robust reproducibility. The clinical sensitivity and specificity were 93.52% and 85.53%, respectively, compared to conventional microbiological or clinical methods. The on‐chip LAMP assay provides an effective dual‐sample and multiple pathogen analysis, and thus would be applicable to on‐site detection and routine monitoring of multiple pathogens in aquaculture.

Habitat fragmentation changes top‐down and bottom‐up controls of food webs - Rong Wang; Xin Zhang; Yi‐Su Shi; Yuan‐Yuan Li; Jianguo Wu; Fangliang He; Xiao‐Yong Chen (Ecology, 2020)
Top‐down and bottom‐up controls regulate the structure and stability of ecosystems, but their relative roles in terrestrial systems have been debated. Here we studied a hydro‐inundated land‐bridge system in subtropical China and tested the relative importance of these two controls in determining the rodent‐mediated regeneration of a locally dominant tree species. Our results showed that both controls operated in terrestrial habitats and that their relative importance switched as habitat size changed. Habitat loss initially removed predators of rodents that released rodent populations and triggered massive seed predation (top‐down control), leading to reduced seedling establishment. A further reduction in habitat size led to decrease in rodent population that was supposed to increase seedling survival of the tree species, but the decline in habitat size deteriorated the abiotic environments (bottom‐up control) that severely prevented seedling recruitment. As the ongoing global land use change is creating increasing number of small‐sized forest fragments, our findings provide novel insights into the restoration of seriously fragmented forests.

Srk1 kinase, a SR protein‐specific kinase, is important for sexual reproduction, plant infection and pre‐mRNA processing in Fusarium graminearum - Guanghui Wang; Peng Sun; Ziwen Gong; Lianfeng Gu; Yi Lou; Wenqin Fang; Lianhu Zhang; Li Su; Tao Yang; Baohua Wang; Jie Zhou; Jin‐Rong Xu; et al. (Environmental Microbiology, 2018)
Summary SR protein‐specific kinases (SRPKs) uniquely with a spacer region are important splicing factors from yeast to human. However, little is known about their biological functions in filamentous fungi. Therefore, we characterized a SRPK called SRK1 in wheat scab fungus Fusarium graminearum . Our data showed that Srk1 is required for vegetative growth, sexual reproduction and plant infection, and plays critical roles in pre‐mRNA alternative splicing and gene expression. Remarkably, we found that Srk1 displayed dynamic shuttling between cytoplasm and the nucleus, which is regulated by the divergent spacer domain rather than its kinase activity, suggesting a regulatory mechanism for Srk1. Interestingly, Srk1‐GFP also localized to the septal pores, indicating a possible role of Srk1 unrelated to mRNA processing. Although both K1 and K2 lobes of the kinase domain are essential for Srk1 functions, the K2 but not K1 lobe is responsible for the septal pore localization. Lastly, we established that Srk1 physically interacts with the two SR proteins, FgNpl3 and FgSrp1. Overall, our results indicated that SRK1 regulates fungal development, plant infection and mRNA processing by phosphorylation of other splicing factors including SR proteins, and the spacer domain regulates the functions of Srk1 by modulating its nucleocytoplasmic shuttling.